Temperature-Sensitive Mutations in the Putative Herpes Simplex Virus Type 1 Terminase Subunits pU(L)15 and pU(L)33 Preclude Viral DNA Cleavage/Packaging and Interaction with pU(L)28 at the Nonpermissive Temperature - Yang, Kui (American Society for Microbiology (ASM), 2008)
Terminases comprise essential components of molecular motors required to package viral DNA into capsids in a variety of DNA virus systems. Previous studies indicated that the herpes simplex virus type 1 U(L)15 protein (pU(L)15) interacts with the pU(L)28 moiety of a pU(L)28-pU(L)33 complex to form the likely viral terminase. In the current study, a novel temperature-sensitive mutant virus was shown to contain a mutation in U(L)33 codon 61 predicted to change threonine to proline. At the nonpermissive temperature, this virus, designated ts8-22, replicated viral DNA and produced capsids that became enveloped at the inner nuclear membrane but failed to form plaques or to cleave or package viral DNA. Incubation at the nonpermissive temperature also precluded coimmunoprecipitation of U(L)33 protein with its normal interaction partners encoded by U(L)28 and U(L)15 in ts8-22-infected cells and with pU(L)28 in transient-expression assays. Moreover, a temperature-sensitive mutation in U(L)15 precluded coimmunoprecipitation of pU(L)15 with the U(L)28 and U(L)33 proteins at the nonpermissive temperature. We conclude that interactions between putative terminase components are tightly linked to successful viral DNA cleavage and packaging.